RELATIONSHIP BETWEEN STRESS AND TEMPOROMANDIBULAR JOINT DISORDERS IN MEDICAL AND DENTISTRY STUDENT OF UNIVERSITAS JENDERAL ACHMAD YANI - Patria Nawawi, Azkya; Arifianti, Isti; Berniqca Amanda, Kayla (Fakultas Kedokteran Gigi Unjani, 2025)
Temporomandibular joint disorder is a condition that is often unrecognized by patients. One of the etiologies of temporomandibular joint disorder is stress. Medical and dental students may experience stress associated with symptoms of temporomandibular joint disorders. The aim of this study was to determine the relationship between stress and temporomandibular joint disorders in dental and medical faculty students. The research design is analytic with a cross-sectional method on 196 students of Medicine and Dentistry at The University Jenderal Achmad Yani, class of 2020. Chi-square analysis was utilized to investigate the relationship between temporomandibular joint disorders and stress. The results indicate a significant association between symptoms of temporomandibular joint disorders and stress (p = 0.002). Stress is one of the etiological factors in the occurrence of temporomandibularjoint disorders. DOI : 10.54052/jhds.v4n3.p301-312